Work experience as an intermediary the influence of work motivation and transformational leadership on teacher performance - Liunokas, Adelina; Pranoto, Yuli Kurniawati Sugiyo; Formen, Ali (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Work motivation drives teachers to perform optimally, while transformational leadership can inspire and empower teachers to achieve shared goals effectively. Therefore, this study aims to analyze how work experience functions as a mediating variable in the relationship between work motivation and transformational leadership on teacher performance. This research uses a quantitative approach with a correlational type of research. The population was 380 teachers with a sample of 190 kindergarten teachers in Kupang City using a random sampling technique using guidance from the Kerjce table. Data collection used an instrument in the form of a questionnaire with 47 items measuring work motivation, transformational leadership, teacher performance with and the work experience. Data were analyzed using multiple linear regression models and path analysis. The results of this study indicate that work motivation and transformational leadership can improve teacher performance directly and indirectly through work experience. This study shows that work motivation and transformational leadership majorly impact school teacher performance. There is a significant effect of work experience in mediating work motivation on teacher performance. In addition, work experience significantly influences and mediates transformational leadership on teacher performance. It is hoped that the results of this study can support the science of human resource management and teacher performance both academic and practical.